Indeks Kepentingan Industri Pelancongan Mampan Pulau Langkawi - Haji Abd Hamid, Mohd Rawi (2019)
While sustainable development is growing rapidly in the tourism industry, there is still gap in integrating sustainability and tourism. Malaysia also do not have a proper sustainable tourism features that can be widely applied by the tourism players in the industry. In light of the importance of the industry to many parties locally and globally,due care must be given to the tourism industry on its impact to sustainable development. It had been noted by previous evidences that sustainable tourism in Malaysia still lagging and slow compared to other countries. The purpose of this study is to determine the features of sustainable tourism that must be applied in sustainable tourism development and can be accepted by tourist and locals to implement sustainable tourism in order to increase the acceptance of sustainable technology in tourism sector. The data collection for this research was done using literature review and questionnaire distribution. The sample population was taken from locals and foreigners visiting Langkawi Island. About 423 survey papers were distributed for both local and tourists and each paper was able to be retrieved back to be analysed. Result from the SPSS software shows only 16 out of 27 sustainable tourism features were accepted by respondents. Most respondents also seem to focus on the aspect of nature in their answers which shows how much they emphasize nature and environmental awareness in sustainable tourism. This study identify the features of sustainable tourism accepted by respondents which can be used and applied in the development of sustainable tourism in Malaysia.